Modelo de gestión por procesos del Cuerpo de Bomberos del Gobierno Autónomo Descentralizado Municipal de Santo Domingo (CB-GADM-SD), año 2014. - Cedeño Barreiro, María Katherine (2014)
The CB-GADM-SD is a public institution aiming to serve the citizens of Santo Domingo de los Tsáchilas with professionalism and quality by means of a process management structure, which to date has no identified or formalized institutional processes; for which reason, the present proposal seeks to strengthen and optimized material resources and time management in order to ensure that the service provided is one of quality. The proposal presented defines each process in the areas of finance, human resources, emergency assistance and prevention, with the establishment of time periods for each step of these processes, alongside indicators which allow the proper evaluation and control of process management for continuous improvement. In this way the proposed objectives are met and an achievable solution for the problem is provided.